Tinjauan Aspek Keamanan dan Kerahasiaan Rekam Medis di Ruang Penyimpanan Rumah Sakit Bina Kasih Pekanbaru Tahun 2024 - Nurjanah, Ana; Trisna, Wen Via (Indonesian of Health Information Management Journal (INOHIM), 2024)
AbstractThe medical record storage room must comply with applicable standards to ensure the security and confidentiality of medical records. At Bina Kasih Hospital, there are still issues with security, such as staff eating and drinking in the storage room, inadequate lighting, and dusty medical records. This study aims to assess the security and confidentiality of medical records in the storage room of Bina Kasih Hospital in Pekanbaru, Riau. The method used is a qualitative approach with a descriptive design. Three informants participated in this study: one head of medical records and two medical record staff. Data were collected through interviews and observation techniques. The study's results showed that, from the physical aspect, the humidity in the storage room was around 50%, and the temperature was around 25˚C, measured using a thermohygrometer. However, the lighting in the room was insufficient due to overcrowded racks, preventing light from spreading correctly. The light intensity was measured at 39 lux near the storage racks and 65 lux near the medical record staff's desk. From the chemical aspect, staff were still eating and drinking in the room. From the biological aspect, some medical records were damaged by termite bites. Regarding the confidentiality of medical records, the storage room door was secured with a fingerprint code that only medical record staff knew, preventing unauthorized personnel from entering without permission. The study concluded that the lighting in the room remains inadequate, staff still eat and drink in the room, and termites damaged some medical records. However, the confidentiality of medical records is well-maintained. It is recommended to add more lighting to the storage room, install "no eating and drinking" signs, and implement insect control every six months.Keywords: security, confidentiality, medical records, storage room AbstrakRuang penyimpanan rekam medis harus sesuai dengan standar yang berlaku guna memastikan keamanan dan kerahasiaan rekam medis tetap terjamin. Rumah Sakit Bina Kasih dari aspek keamanan masih ada petugas makan dan minum dalam ruang penyimpanan, pencahayaan kurang dan rekam medis berdebu. Tujuan penelitian untuk mengetahui keamanan dan kerahasiaan rekam medis di ruang penyimpanan Rumah Sakit Bina Kasih Pekanbaru Riau. Metode yang digunakan adalah pendekatan kualitatif dengan desain deskriptif. Tiga informan yang terlibat dalam penelitian ini terdiri dari 1 kepala rekam medis dan 2 petugas rekam medis. Data dikumpulkan melalui teknik wawancara dan observasi. Hasil penelitian menunjukkan aspek fisik kelembaban di ruang penyimpanan berkisar 50% suhu berkisar 25˚C dengan menggunakan alat bantu pengukur kelembaban dan suhu yaitu thermohygrometer, sedangkan pencahayaan di ruangan masih kurang karena rak-rak yang ada di dalam ruangan terlalu padat, sehingga cahaya tidak dapat menyebar dengan baik. Intesitas cahaya 39 lux dekat rak penyimpanan dan 65 lux dekat meja petugas rekam medis. Aspek kimawi, masih ada petugas rekam medis makan dan minum dalam ruangan. Aspek biologis, terdapat rekam medis terkena gigitan rayap. Kerahasiaan rekam medis, pintu ruang penyimpanan sudah menggunakan kode finger print yang hanya diketahui oleh petugas rekam medis sehingga petugas lain tidak bisa masuk tanpa seizin petugas rekam medis. Kesimpulan penelitian penerangan dalam ruangan masih kurang, petugas rekam medis masih makan dan minum dalam ruangan, terdapat rekam medis terkena gigitan rayap, kerahasiaan rekam medis sudah baik. Sebaiknya, ditambahkan lampu dalam ruang penyimpanan, dibuat tulisan dilarang makan dan minum, dilakukan pengendalian serangga 6 bulan sekali.Kata Kunci: keamanan, kerahasiaan, rekam medis, ruang penyimpanan